2020
DOI: 10.1080/14616696.2020.1833065
|View full text |Cite
|
Sign up to set email alerts
|

The Covid-19 crisis: the end of a borderless Europe?

Abstract: This article reflects on the impact of the coronavirus pandemic and border control measures on the narratives and experience of territorial borders and the social construction of boundaries. The Covid-19 crisis has revealed how strong and durable territorial borders still are and how rapidly the idea of a borderless Europe might change in divided Europe. The imposition of border controls and the temporary closure of borders in order to prevent the spread of the coronavirus was particularly problematic for bord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 15 publications
1
44
0
5
Order By: Relevance
“…The included studies reported on the implementation of international travel measures in Brazil, 47 Canada, 36 France, 36 Germany, 36 , 48 Italy, 36 Japan, 36 , 37 Malaysia, 51 Nepal, 52 Poland, 48 , 54 South Africa, 37 Turkey, 53 Vietnam, 49 the UK 36 , 37 and the USA. 33 , 36 , 37 , 46 , 49 , 50 Eight studies analysed the effects of international travel measures implemented by multiple countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies reported on the implementation of international travel measures in Brazil, 47 Canada, 36 France, 36 Germany, 36 , 48 Italy, 36 Japan, 36 , 37 Malaysia, 51 Nepal, 52 Poland, 48 , 54 South Africa, 37 Turkey, 53 Vietnam, 49 the UK 36 , 37 and the USA. 33 , 36 , 37 , 46 , 49 , 50 Eight studies analysed the effects of international travel measures implemented by multiple countries.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported on the countries that were targeted by the measures, notably China, 33 , 44 Germany, 48 India, 52 Iran, 44 Italy, 44 Poland, 48 , 54 South Korea 44 and the UK. 46 However, in the majority of studies, this was either not applicable or not specified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the relatively recent outbreak of this health crisis, there have been few robust research projects finished so far. We can work, however, with the first reactions in the form of scientific articles (Medeiros et al, 2020;Opiłowska, 2020), blogs and non-peer-reviewed papers (Klatt, 2020;Jańczak, 2020;Berrod and Bruyas, 2020;Böhm, 2020). They observed massive rebordering tendencies, as most of the measures based on social distancing were introduced on a strictly national basis and contradicted steps desired by the European institutions (Brunet-Jailly and Vannet, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the pandemic has introduced a new level of uncertainty in all internationalincluding cross-border -affairs and led many to question whether citizens will be able to continue enjoying the freedom of movement once the crisis is over (Calzada, 2020). Nevertheless, the pandemic also pointed to high levels of cross-border integration in some European cross-border regions, where the locals voiced themselves loudly against the closed borders (Opiłowska, 2020).…”
Section: Introductionmentioning
confidence: 99%